Chronotropic response of beta-adrenergic-, muscarinic-, and calcitonin gene-related peptide-receptor agonists in right atria from neonatal capsaicin-treated rats - Gasparetti, A. L.; Hyslop, S.; Costa, SKP; Priviero, FBM; De Nucci, G.; Antunes, E.; Zanesco, A. (Elsevier B.V., 2002)
We evaluated the potency of isoproterenol, carbachol, pilocarpine and calcitonin gene-related peptide (CGRP) in the rat right atria at 30, 60 and 90 days after neonatal capsaicin treatment. Neonatal rats were pretreated on the second day of life with capsaicin (50 mg/kg). The capsaicin pretreatment caused a five-fold rightward shift at the pEC(50) level on the concentration-response curves to isoproterenol in 30-day-old rats. Propranolol (10 mg/kg, given 15 min prior to capsaicin treatment) prevented this subsensitivity. No changes in the potency of isoproterenol were observed at 60 and 90 days after capsaicin pretreatment. The potency and maximal responses of CGRP in the right atria in 30-day-old rats were significantly higher than in 60- and 90-day-old rats; however, no differences were found between control and capsaicin groups. The potency and maximal responses to carbachol and pilocarpine were not changed in all groups. The neonatal capsaicin treatment reduced by about 74% the CGRP content in the heart in all groups. In summary, capsaicin treatment in newborn rats produces a desensitization of chronotropic response mediated by beta-adrenoceptors in isolated right atria from 30-day-old rats possibly due to a massive release of catecholamines. (C) 2002 Elsevier B.V. Ireland Ltd. All rights reserved.
Keywords: capsaicin; sensory fibers; beta-adrenoceptors; muscarinic receptors; heart; chronotropic response; right atria